Perbandingan Hasil Belajar Siswa Melalui Penggunaan Media Poster Berbasis Ppt Interaktif dan Media Video Animasi pada Muatan IPS Kelas IV di SD - Yesita Galatia Maysella; Syaiful Imam; Puri Selfi Cholifah; Yesita Galatia Maysella; Syaiful Imam (Universitas Negeri Malang, 2021)
Abstract: This research was conducted with the aim of comparing the learning outcomes between students using PowerPoint-based poster learning media with animated video media in social studies subject class IV material